Experimental and numerical investigation of metal foams undergoing large deformations. Issue 1 (October 2016) - Heinze, Stephan; Jung, Anne; Diebels, Stefan; Düster, Alexander
Abstract: Open cell aluminum metal foams are a new kind of material that are used in composite structures to reduce their weight, to increase their sound or energy absorption capability or to decrease their thermal conductivity. The design and analysis of such structures requires a macroscopic constitutive model of the foam that has to be determined by various experiments under different loading conditions. We support this procedure by analyzing the microstructure of the metal foam numerically under large deformations. To this end, we employ the finite cell method that can deal with large deformations and allows for an automatic and efficient discretization of the CT‐image of the foam. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)